Wayne's world ; Wayne's world 2 [videorecording (Blu-Ray)] / Paramount Pictures presents a Lorne Michaels production. - Myers, Mike, 1963- (Paramount Pictures, 2022)
Wayne's world: Best friends Wayne Campbell and Garth Algar host their own public-access television show, "Wayne's World." Television producer Benjamin Kane wants to take the show to the world of commercial television. Wayne and Garth battle to save their show and Wayne's girlfriend from Benjamin.